THE DIRE NEED OF URGENT CARE CENTERS IN PAKISTAN; A POTENTIAL SOLUTION TO EMERGENCY ROOM OVERCROWDING - Husseni, Aisha Maryam; Ullah, Muhammad Anzar (Journal of Ayub Medical College Abbottabad, 2019)
An urgent care center can be defined as an alternative to the emergency department for traumatic/non-traumatic conditions that do not require life-saving measures. According to Urgent Care Association of America (UCAOA), An urgent care center is a medical clinic with expanded hours that is specially equipped to diagnose and treat a broad spectrum of non-life and limb threatening illnesses and injuries.1 Urgent care first came to light in the 1970s with the aim of meeting immediate health care requirements.2 The first urgent care center was opened in the United States in the early 1980s.3 These centers accept unscheduled walk-in patients on a first-come, first-serve basis.4 This facility is far more cost effective than the emergency department.2 According to recent statistics, the emergency room is on average 3-4 times more expensive than an urgent care center for conditions like sore throat, UTIs etc.2 Another study conducted by Robin M. Weinick et Al states that 13-27% of all emergency room visits could be treated at an urgent care center or a retail clinic. This could save about 4.4 billion dollars in the United States each year.5 This method of care has proven to be more patient-friendly for those who wish to be treated immediately but also who do not have a life-threatening condition. Furthermore, urgent care centers are facilitated with many equipment such as X-ray and on-site services like a laboratory which speeds up the diagnosis and treatment.1 Emergency room overcrowding is a serious global issue faced by developed as well as developing countries like Canada, Saudi Arabia, Finland, Denmark and India etc.6 It was called a major problem in the United States by the Institute of Medicine in 2006. This leads to access block which means that patients have to wait for long hours after presentation to receive medical care.7 High patient influx and long waiting hours have led to poor prognosis and a potential increase in patient mortality.8,9 In the United states, there have been multiple studies on ER overcrowding which emphasize its highly negative effect on patient care such as medication errors10, patient mortality, lack of efficiency and timely care11. One major causative factor that has come to attention is boarding which leads to patient infiltration in the ER due to the lack of in-patient beds. This problem was particularly witnessed in Australia.6 Another cause is the improper use of the emergency room.6 Patients tend to overestimate their illness, causing overcrowding in the ER.12 Many people come to the ER with non-emergent and less severe complaints that could be handled in any other setting, perhaps an urgent care unit.5 Another study also states that many emergency room admissions are due to minor injuries or illnesses.7 Interestingly, a study conducted by Morphet J. et al found that majority of the patients who were admitted in emergency rooms were due to limb injury/limb pain and falls. The interventions for such injuries used were supportive bandages, slings and zimmer splints.13 Such patients also do not need to undergo the hassle of a traumatic emergency room experience. Pakistan is also not spared by this menace. Overpopulation and limited resources in both private and government setups have led to significant ER over-crowding. According to a news report, a 2000 bedded ER of a tertiary care hospital in Lahore caters to around 3000 patients every day, while another tertiary care hospital in the same city has around 80 beds and receives a daily influx of around 500 patients in its ER.14 Moreover, a major pediatric hospital in Karachi also witnesses ER overcrowding due to similar reasons.15 According to American College of Emergency Physicians (ACEP), overcrowding occurs when the need for emergency services exhausts the available resources in the ER.16 Considering this statement, almost every major tertiary care hospital in Pakistan is facing this problem. Insufficient health budget, scarcity of resources and understaffing in hospitals have already deteriorated the health system of Pakistan.17 ER overcrowding is like a catalyst to these problems. From contaminated stretchers18 and staff exhaustion to patient dissatisfaction due to improper pain management and long waiting hours, all have progressed to poor ER outcomes.16,19 In lieu of these problems, an alternative measure should be implemented. Although an urgent care center is not the only solution, similar facilities like the ’˜fast-track systems’ have proven to be very effective. It attends to low-acuity patients, in order to lower the burden on the ER.20 Since 2002, The UK National Health Service (NHS) has also promoted fast-track systems.7 Habib M.I. et al has also suggested in his study that a day care unit outside the ER should be established for patients who are coming in for minor treatments like nebulization, IV and IM medications in order to reduce overcrowding and the burden on ER staff. This again proposes the establishment of urgent care units in hospitals. However, another study states that such systems fail when there is a high influx of seriously ill patients in the ER as all the staff gets occupied in managing such patients.21 Urgent care centers can be the stepping stone in improving the already deteriorating health system of Pakistan but this system has its own limitations and is not the only cure for this dreadful crisis.